Radical-scavenging activity and antibacterial activity of crude ethanolic leaf extract of sili (Capsicum frutescens). - Redil, Richard D.; Ricarte, Marjhun A. (Richard D. Redil, 2018)
The radical-scavenging activity and antibacterial activity of Capsicum frutescens leaves were examined in this study. The radical-scavenging properties of crude ethanolic leaf extracts were determined using the DPPH-radical (2,2-diphenyl-l-picrylhydrazyl) scavenging assay with gallic acid (EC50= 6.67 +/- 0.12 ppm) and quercetin (EC50= 4.75 +/- 0.19 ppm) as standards. The crude plant extract of the leaves of C. annuum gave an EC50 value of 1280.51 +/- 34.12 ppm. The antibacterial property of the plants were screened against Gram-negative (Eschirichia coli) and Gram-positive (Staphylococcus aureus) bacteria using disk-diffusion assay. The crude extract exhibited inhibitory activities on the two species of bacteria. Thin layer chromatographic analyses were done on leaf extracts using gallic acid (phenolic acid) and quercetin (flavonoid) as representative standards. Among the different solvent systems used, benzene-chloroform-methanol (2:8.5:3) produced the best separation for the plant extract. The extract was found to possibly contain flavonoids, which could account for the radical scavenging activity and antibacterial property of the plant leaf, and a variety of unknown components that could have influenced the activities of the plant extract. Based on the results of the study, the plant extract contain several phytochemicals that may be responsible for the radical-scavenging and antibacterial activities observed.
A research paper (B.S. Biology) -- University of the Philippines, Tacloban.